2019
DOI: 10.1155/2019/5758437
|View full text |Cite
|
Sign up to set email alerts
|

Using Burstiness for Network Applications Classification

Abstract: Network traffic classification is a vital task for service operators, network engineers, and security specialists to manage network traffic, design networks, and detect threats. Identifying the type/name of applications that generate traffic is a challenging task as encrypting traffic becomes the norm for Internet communication. Therefore, relying on conventional techniques such as deep packet inspection (DPI) or port numbers is not efficient anymore. This paper proposes a novel flow statistical-based set of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…where 𝛿𝑡 đť‘– = element in the time_delta list from L1 service filter, Based on our study, application service traffic occurs in a burst that is recognizable within the standard deviation of its interarrival times. This is also in line with a recent study that identified application traffic through its burstiness [33]. However, it is also worth noting that there is a micro delay between exact service execution and packet capture time.…”
Section: Service Isolator Enginesupporting
confidence: 90%
“…where 𝛿𝑡 đť‘– = element in the time_delta list from L1 service filter, Based on our study, application service traffic occurs in a burst that is recognizable within the standard deviation of its interarrival times. This is also in line with a recent study that identified application traffic through its burstiness [33]. However, it is also worth noting that there is a micro delay between exact service execution and packet capture time.…”
Section: Service Isolator Enginesupporting
confidence: 90%